Gilles de la Tourette Syndrome: Clinical Features of 75 Cases from Argentina - F. Micheli; M. Gatto; O. Gershanik; A. Steinschnaider; M. Fernandez Pardal; M. Massaro (Behavioural Neurology)
A series of 75 cases of Gilles de la Tourette syndrome (GTS) from Argentina, whose ages ranged from 6 to 55 with a mean of 20.02, were evaluated to compare findings with those reported for other countries. Mean age at onset was 7.44 years and mean overall duration of symptoms was 12.58 years; 6.7% of cases were mild, 49% moderate and 44.3% severe. Most frequent presenting motor tics were excessive blinking in 41 followed by head jerking in 16 and eye winking in six, while phonic tics included coprolalia in 28.0%, echolalia in 17.5% and palilalia in 10.8%. Abnormal perinatal events were reported in 40.5%, while positive family history for tics was present in 26.66%. Obsessive–compulsive behaviour was evident in 66% and attention deficit disorder in 16% of cases. Self-injurious behaviour comprised onychophagia in 28 patients, lip-biting in seven and self-slapping in eight cases. Almost half of our patients were initially interpreted as having a psychogenic disorder indicating that GTS in Argentina is most likely underdiagnosed. It may be concluded that the overall pattern of GTS is not dissimilar to that described for European, Asian and American populations, thus highlighting the previously recognized cross-cultural uniformity.